2015
DOI: 10.1093/eurheartj/ehv695
|View full text |Cite
|
Sign up to set email alerts
|

The genetics underlying acquired long QT syndrome: impact for genetic screening

Abstract: A third of aLQTS patients carry cLQTS mutations, those on KCNH2 being more common. The probability of being a carrier of cLQTS disease-causing mutations can be predicted by simple clinical parameters, thus allowing possibly cost-effective genetic testing leading to cascade screening for identification of additional at-risk family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 29 publications
1
145
0
4
Order By: Relevance
“…In addition, hiPSC‐CMs are also being used as model systems to test the effect of both known and novel drugs on cardiac channelopathies (Matsa et al , 2011; Zhang et al , 2012; Bellin et al , 2013; Di Pasquale et al , 2013; Zhang et al , 2014), with suppression of pathological pro‐arrhythmic potential and restoration of altered AP duration (APD) being two main endpoints. Clinical evidence has shown that pharmacological treatments can be of more benefit when properly calibrated in a disease‐specific or even mutation‐specific manner (Nebert and Vesell, 2006; Cavallari, 2012; Amin and Wilde, 2016; Itoh et al , 2016; Martiniano et al , 2016). This has been particularly evident for monogenic diseases targeting the cardiac electrical system (Priori, 1998; Tan et al , 2006), because genetic modifiers critically determine the clinical phenotype (Duchatelet et al , 2013; de Villiers et al , 2014).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
“…In addition, hiPSC‐CMs are also being used as model systems to test the effect of both known and novel drugs on cardiac channelopathies (Matsa et al , 2011; Zhang et al , 2012; Bellin et al , 2013; Di Pasquale et al , 2013; Zhang et al , 2014), with suppression of pathological pro‐arrhythmic potential and restoration of altered AP duration (APD) being two main endpoints. Clinical evidence has shown that pharmacological treatments can be of more benefit when properly calibrated in a disease‐specific or even mutation‐specific manner (Nebert and Vesell, 2006; Cavallari, 2012; Amin and Wilde, 2016; Itoh et al , 2016; Martiniano et al , 2016). This has been particularly evident for monogenic diseases targeting the cardiac electrical system (Priori, 1998; Tan et al , 2006), because genetic modifiers critically determine the clinical phenotype (Duchatelet et al , 2013; de Villiers et al , 2014).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
“…Candidate gene screening studies have been performed to explain diLQTS in large cohorts of patients as a form frustre of congenital LQTS. However, the prevalence of common mutations in the known LQTS genes was limited (from 10 to maximum 30%) [31][32][33][34]. As exemplified in our study, many subjects developing profound changes in cardiac repolarization in response to a pharmacological challenge do not present with clinical or electrocardiographic abnormalities at baseline, nor have familial history of syncope or sudden death [31][32][33][34].…”
Section: Discussionmentioning
confidence: 61%
“…However, the prevalence of common mutations in the known LQTS genes was limited (from 10 to maximum 30%) [31][32][33][34]. As exemplified in our study, many subjects developing profound changes in cardiac repolarization in response to a pharmacological challenge do not present with clinical or electrocardiographic abnormalities at baseline, nor have familial history of syncope or sudden death [31][32][33][34]. In a recent study with a Danish population cohort of 7000 subjects, Ghouse et al found that 26 congenital LQTS-associated variants (mainly affecting ion channels) did not influence QTc interval duration, syncopes or overall mortality [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of references, novel variants were included when they were deemed to be pathogenic or likely pathogenic by applying the recently published ACMG guidelines, 18 which are based on criteria using typical types of variant evidence, including the frequencies in the population data and computational (in silico) predictive programs. 19 …”
Section: Clinical Course During the Follow-upmentioning
confidence: 99%